Dramatherapy : reflections and praxis - Hougham, Richard Ed; Jones, Bryn, Ed (Palgrave, 2017)
A critical and cohesive collection of interdisciplinary perspectives on Dramatherapy as it is being practiced, developed and advanced today. Unpicking the relationship between drama and therapy, exploring its key philosophies and practices, and examining its efficacy, the text is a crucial resource for students and practitioners in a growing field."--Provided by publisher.